Polymer, composition, composite piezoelectric body, piezoelectric thin film, and piezoelectric element

By using a polymer of cyanoethyl and hydrophobic repeating units in a specific ratio to form a piezoelectric thin film with piezoelectric particles, the problems of large changes in dielectric constant and wrinkling under high temperature and high humidity environments were solved, and stable thin film performance was achieved.

CN119278220APending Publication Date: 2025-01-07FUJIFILM CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380043014.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-30
Filing Date
2023-06-16
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing high dielectric constant materials exhibit significant changes in relative dielectric constant and are prone to wrinkling under high temperature and high humidity environments, making it difficult to meet performance requirements.

Method used

A piezoelectric thin film is formed by combining a polymer containing cyanoethyl repeating units and hydrophobic repeating units in a specific ratio with piezoelectric particles and an electrode layer to suppress changes in relative permittivity and the formation of wrinkles.

Benefits of technology

Under high temperature and high humidity conditions, the relative permittivity changes little, the thin film has fewer wrinkles, and the performance is stable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278220A_ABST
    Figure CN119278220A_ABST
Patent Text Reader

Abstract

The present invention provides a polymer, a composition, a composite piezoelectric body, a piezoelectric thin film, and a piezoelectric element which can form a thin film having little change in relative permittivity before and after exposure to a high-temperature and high-humidity environment and having few wrinkles. This polymer contains a repeating unit represented by formula (A) and a repeating unit represented by formula (B), the content of the repeating unit represented by formula (A) being 60 mol% or more with respect to all the repeating units of the polymer, the content of the repeating unit represented by formula (B) being 1-40 mol% with respect to all the repeating units of the polymer, and the content of the repeating unit represented by formula (B) being 1-40 mol% with respect to all the repeating units of the polymer. The polymer does not contain a repeating unit represented by formula (C), or when the polymer contains a repeating unit represented by formula (C), the content of the repeating unit represented by formula (C) is 5 mol% or less with respect to all repeating units of the polymer. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a polymer, a composition, a composite piezoelectric body, a piezoelectric film and a piezoelectric element. Background Art

[0002] Conventionally, cyanoethyl compounds and the like are known as organic materials having a high relative dielectric constant and are suitable for various applications such as organic electroluminescent elements and capacitors.

[0003] As such a material with a high relative dielectric constant, for example, Patent Document 1 discloses "a high dielectric constant, characterized in that a compound selected from oligosaccharides, polysaccharides, polyvinyl alcohol and their derivatives is substituted by a cyanoethyl group and a saturated fatty acid ester group having 10 to 20 carbon atoms, the substitution rate of the cyanoethyl group is 60% or more, and the substitution rate of the saturated fatty acid ester group having 10 to 20 carbon atoms is 5 to 40%."

[0004] Previous technical literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 6-196022 Summary of the invention

[0007] Technical issues to be solved by the invention

[0008] On the other hand, in recent years, there has been an increasing demand for further improvement in the performance of such materials having a high relative dielectric constant.

[0009] For example, it is desirable that the relative dielectric constant of the material be less changed before and after the material is exposed to a high temperature and high humidity environment, and it is also desirable that the occurrence of shape defects such as wrinkles in a film containing the material be suppressed.

[0010] The present inventors have studied the properties of the high dielectric constant described in Patent Document 1 and have found that the high dielectric constant cannot fully satisfy the above-mentioned required properties and further improvements are required.

[0011] An object of the present invention is to provide a polymer capable of forming a thin film having a small change in relative dielectric constant and few wrinkles before and after exposure to a high-temperature and high-humidity environment.

[0012] In summary, the present invention also aims to provide a composition, a composite piezoelectric body, a piezoelectric film and a piezoelectric element.

[0013] Means for solving technical problems

[0014] In order to solve the problem, the present invention has the following structure.

[0015] (1) A polymer comprising a repeating unit represented by the formula (A) described below and a repeating unit represented by the formula (B) described below, wherein:

[0016] The content of the repeating unit represented by formula (A) is 60 mol% or more relative to all the repeating units of the polymer,

[0017] The content of the repeating unit represented by formula (B) is 1 to 40 mol% relative to all the repeating units of the polymer.

[0018] The polymer does not contain a repeating unit represented by formula (C) described below, or

[0019] In the case where the polymer contains the repeating unit represented by the formula (C), the content of the repeating unit represented by the formula (C) is 5 mol% or less relative to all the repeating units of the polymer.

[0020] (2) The polymer according to (1), wherein

[0021] The aliphatic hydrocarbon group which may have a substituent has 2 to 8 carbon atoms.

[0022] (3) The polymer according to (1) or (2), wherein

[0023] The content of the repeating unit represented by formula (A) is 70 mol% or more relative to all the repeating units of the polymer,

[0024] The content of the repeating unit represented by the formula (B) is 1 to 30 mol% based on all the repeating units of the polymer.

[0025] (4) A composition comprising the polymer according to any one of (1) to (3) and a cyano group-containing compound different from the polymer.

[0026] (5) The composition according to (4), wherein

[0027] The cyano group-containing compound is a compound represented by the formula (1) described later.

[0028] (6) The composition according to (4) or (5), wherein

[0029] The cyanide-containing compound is cyanoethyl sucrose.

[0030] (7) A composite piezoelectric body comprising the polymer according to any one of (1) to (3) and piezoelectric particles.

[0031] (8) The composite piezoelectric body according to (7), wherein:

[0032] The piezoelectric particles include ceramic particles having a perovskite-type or wurtzite-type crystal structure.

[0033] (9) The composite piezoelectric body according to (7) or (8), wherein:

[0034] The piezoelectric particles include any one of lead zirconate titanate, lead lanthanum zirconate titanate (PLZT), barium titanate, zinc oxide, and a solid solution of barium titanate and bismuth ferrite.

[0035] (10) The composite piezoelectric body according to any one of (7) to (9), further comprising a cyano group-containing compound different from the polymer.

[0036] (11) A piezoelectric film having:

[0037] A piezoelectric layer comprising the composite piezoelectric body described in any one of (7) to (10); and

[0038] Electrode layers provided on both sides of the piezoelectric layer.

[0039] (12) A piezoelectric element comprising the piezoelectric film described in (11).

[0040] Effects of the Invention

[0041] According to the present invention, it is possible to provide a polymer capable of forming a thin film having a small change in relative dielectric constant and few wrinkles before and after exposure to a high-temperature and high-humidity environment.

[0042] Furthermore, according to the present invention, a composition, a composite piezoelectric body, a piezoelectric thin film, and a piezoelectric element can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 This is a diagram schematically showing an example of the piezoelectric film of the present invention.

[0044] Figure 2 This is a conceptual diagram for explaining an example of a method for producing a piezoelectric thin film.

[0045] Figure 3 This is a conceptual diagram for explaining an example of a method for producing a piezoelectric thin film.

[0046] Figure 4 This is a conceptual diagram for explaining an example of a method for producing a piezoelectric thin film.

[0047] Figure 5 This is a diagram conceptually showing an example of a piezoelectric speaker using a piezoelectric film. DETAILED DESCRIPTION

[0048] Hereinafter, the polymer, composition, composite piezoelectric body, piezoelectric film, and piezoelectric element of the present invention will be described in detail based on the preferred embodiments shown in the accompanying drawings.

[0049] Although the description of the constituent elements described below may be made based on representative embodiments of the present invention, the present invention is not limited to such embodiments.

[0050] In addition, in this specification, the numerical range expressed by "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0051] Furthermore, unless otherwise specified, the bonding direction of the divalent groups marked in this specification is not limited. For example, when Y in the compound represented by the general formula "XYZ" is -COO-, Y may be -CO-O- or -O-CO-. That is, the above compound may be "X-CO-OZ" or "XO-CO-Z".

[0052] As a characteristic point of the polymer of the present invention, it can be cited that it contains a specified amount of a specified repeating unit. The repeating unit represented by formula (A) is a repeating unit related to dielectric properties. By containing a specified amount or more of the repeating unit represented by the formula (A), an excellent relative dielectric constant can be achieved. In addition, the repeating unit represented by formula (B) is a repeating unit that can impart hydrophobicity to the polymer. In contrast, the repeating unit represented by formula (C) is equivalent to a repeating unit that can impart hydrophilicity to the polymer. In the present invention, by adjusting the content of the repeating unit represented by formula (B) and the repeating unit represented by formula (C), the change in relative dielectric constant can be reduced before and after the polymer is exposed to a high temperature and high humidity environment, and wrinkles can be suppressed in a film containing the polymer. In particular, it was found that by adjusting the number of carbon atoms of the group represented by R in the repeating unit represented by formula (B) within a specified range, the generation of wrinkles in a film containing a polymer can be suppressed. Although the details of the reason why the generation of such wrinkles is suppressed are not clear, it is presumed that the thermal and mechanical properties of the polymer are adjusted by adjusting the number of carbon atoms in the group represented by R, thereby suppressing the generation of wrinkles.

[0053] <Polymer>

[0054] The polymer of the present invention (hereinafter also referred to as "polymer") is a polymer comprising a repeating unit represented by formula (A) and a repeating unit represented by formula (B), wherein the content of the repeating unit represented by formula (A) is 60 mol% or more relative to all repeating units of the polymer, the content of the repeating unit represented by formula (B) is 1 to 40 mol% or more relative to all repeating units of the polymer, and the polymer does not contain a repeating unit represented by formula (C), or when the polymer contains a repeating unit represented by formula (C), the content of the repeating unit represented by formula (C) is 5 mol% or less relative to all repeating units of the polymer.

[0055] Hereinafter, the characteristics of the polymer will be described in detail.

[0056] [Chemical formula 1]

[0057]

[0058] (Repeating unit represented by formula (A))

[0059] The repeating unit represented by the formula (A) is a repeating unit having a cyanoethyl group.

[0060] From the viewpoint of being able to obtain at least one of the following effects: the content of the repeating unit represented by formula (A) is 60 mol % or more relative to all the repeating units of the polymer, a smaller change in the relative dielectric constant before and after exposure to a high temperature and high humidity environment, and a film with fewer wrinkles (hereinafter also referred to as "the viewpoint that the effect of the present invention is more excellent"), it is preferably 70 mol % or more, and more preferably 80 mol % or more.

[0061] The upper limit of the content of the repeating unit represented by the formula (A) is not particularly limited, but is preferably 99 mol% or less, more preferably 98 mol% or less, based on all repeating units in the polymer.

[0062] (Repeating unit represented by formula (B))

[0063] In formula (B), R represents an aliphatic hydrocarbon group which may have a substituent.

[0064] The aliphatic hydrocarbon group may be linear, branched, or cyclic, but a linear one is preferred from the viewpoint of achieving more excellent effects of the present invention.

[0065] The aliphatic hydrocarbon group may be a saturated aliphatic hydrocarbon group or an unsaturated aliphatic hydrocarbon group. Among them, the aliphatic hydrocarbon group is preferably an alkyl group. That is, as R, an alkyl group which may have a substituent is preferred.

[0066] The types of substituents that the aliphatic hydrocarbon group may have are not particularly limited, and examples thereof include aryl, amino, alkoxy, aryloxy, aromatic heterocyclic oxy, acyl, alkoxycarbonyl, aryloxycarbonyl, acyloxy, acylamino, alkoxycarbonylamino, aryloxycarbonylamino, alkylthio, arylthio, aromatic heterocyclic thio, urea, halogen atoms, cyano, hydrazine, heterocyclic groups (e.g., heteroaryl), silyl, and combinations thereof.

[0067] Among them, as the substituent, polymerizable groups such as acryloyl and methacryloyl are preferred.

[0068] The number of carbon atoms of the aliphatic hydrocarbon group which may have a substituent represented by R is 1 to 8, preferably 2 to 8, and more preferably 2 to 5 from the viewpoint of achieving more excellent effects of the present invention.

[0069] In addition, the above-mentioned number of carbon atoms refers to the number of carbon atoms contained in the aliphatic hydrocarbon group that may have a substituent as a whole. Therefore, when the aliphatic hydrocarbon group that may have a substituent does not have a substituent (that is, when R is an unsubstituted aliphatic hydrocarbon group), it means that the number of carbon atoms contained in the aliphatic hydrocarbon group itself is 1 to 8. And, when the aliphatic hydrocarbon group that may have a substituent has a substituent (that is, when R is an aliphatic hydrocarbon group with a substituent), it means that the total number of carbon atoms contained in the aliphatic hydrocarbon group and the number of carbon atoms contained in the substituent is 1 to 8. For example, in the case where R is an ethyl group having an acryloyl group (CH2=CH-CO-), the total number of carbon atoms is calculated as 5 as the total of 3 in the acryloyl group and 2 in the ethyl group.

[0070] The content of the repeating unit represented by formula (B) is 1 to 40 mol % based on all repeating units in the polymer, preferably 1 to 30 mol %, more preferably 5 to 30 mol % from the viewpoint of more excellent effects of the present invention.

[0071] (Repeating unit represented by formula (C))

[0072] The polymer may or may not contain a repeating unit represented by formula (C). However, from the viewpoint of achieving more excellent effects of the present invention, the polymer preferably does not contain a repeating unit represented by formula (C).

[0073] When the polymer contains a repeating unit represented by formula (C), the content of the repeating unit represented by formula (C) is 5 mol% or less, preferably 0.5 to 5 mol%, more preferably 1 to 3 mol%, based on all repeating units of the polymer.

[0074] The total content of the repeating unit represented by formula (A), the repeating unit represented by formula (B), and the repeating unit represented by formula (C) is preferably 90 mol% or more, more preferably 95 mol% or more, based on all the repeating units in the polymer.

[0075] The upper limit of the above-mentioned total content is not particularly limited, and 100 mol % is exemplified.

[0076] The polymer may contain other repeating units in addition to the repeating unit represented by formula (A), the repeating unit represented by formula (B), and the repeating unit represented by formula (C).

[0077] The weight average molecular weight of the polymer is not particularly limited, but is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000 from the viewpoint of achieving more excellent effects of the present invention.

[0078] In this specification, the weight average molecular weight of a polymer is measured by the following apparatus and conditions.

[0079] Measuring device: Trade name "HLC-8420GPC" (manufactured by Tosoh Corporation)

[0080] Column: 3 TOSOH TSKgel SuperAWM-H (manufactured by Tosoh Corporation) connected

[0081] Measurement temperature: 40℃

[0082] Eluent: N-methylpyrrolidone, lithium bromide 10 mM, sample concentration 0.1-0.2 mass %

[0083] Flow rate: 0.5mL / min

[0084] Detector: UV-VIS detector (trade name "UV-8420", manufactured by Tosoh Corporation)

[0085] Molecular weight: Standard polystyrene conversion

[0086] The glass transition temperature of the polymer is not particularly limited, but is preferably 5° C. or higher, more preferably 10° C. or higher, further preferably 20° C. or higher, and particularly preferably 30° C. or higher, from the viewpoint of better shape characteristics of a film containing the polymer. The upper limit is not particularly limited, but is preferably 60° C. or lower, more preferably 50° C. or lower, from the viewpoint of operability.

[0087] The glass transition temperature can be measured by DMA (dynamic viscoelasticity measurement) using a dynamic viscoelasticity measuring device (Rheogel-E4000, manufactured by UBM Co., Ltd.). Specifically, a plate-like sample with a thickness of 0.2 mm, a width of 5 mm, and a length of 10 mm is prepared using the polymer to be measured, and the obtained sample is scanned at a temperature of -50 to 150° C., and the dynamic viscoelasticity measurement is performed by setting the cycle of applied pressure to 1 Hz, and the temperature showing the maximum tan δ value is set as the glass transition temperature.

[0088] The polymer can be synthesized by a known method.

[0089] An example of the polymer is shown below. The structural formula of each repeating unit contained in the polymer is shown below.

[0090] [Chemical formula 2]

[0091]

[0092] <Composition>

[0093] The composition of the present invention comprises the above-mentioned polymer and a cyano group-containing compound different from the above-mentioned polymer.

[0094] The description of the polymer is as described above.

[0095] The content of the polymer in the composition is not particularly limited, but is preferably 1 to 99% by mass, more preferably 50 to 95% by mass, relative to the total mass of the composition. From the viewpoint of suppressing the generation of wrinkles in a film formed using the composition, it is further preferably 60 to 95% by mass. From the viewpoint of small change in relative dielectric constant before and after the composition is exposed to a high temperature and high humidity environment, it is particularly preferably more than 70% by mass and less than 95% by mass, and most preferably 80 to 95% by mass.

[0096] The structure of the cyano group-containing compound is not particularly limited as long as it is a compound having a cyano group and different from the above-mentioned polymer.

[0097] The cyano group-containing compound may be a low-molecular compound having no repeating unit or a high-molecular compound having a repeating unit.

[0098] From the viewpoint of obtaining a more excellent relative dielectric constant of the composition, the cyano group-containing compound preferably has a cyanoethyl group (CN-C2H5-*. * indicates a bonding position).

[0099] The molecular weight of the cyano group-containing compound is not particularly limited, but is preferably not more than 2000. The lower limit is not particularly limited, but is preferably not less than 100.

[0100] The cyano group-containing compound is preferably a compound that is liquid at 20°C.

[0101] The cyano group content in the cyano group-containing compound is not particularly limited, but is preferably 1 to 30 mmol / g, more preferably 5 to 20 mmol / g, from the viewpoint of obtaining a more excellent relative dielectric constant of the composition.

[0102] The cyano group content can be calculated by the following formula based on the molar mass of the cyano group-containing compound and the number of cyano groups (CN number).

[0103] Cyano content = {1 / (molar mass of cyano compound)} × number of CN × 1000

[0104] As the cyano group-containing compound, a compound represented by formula (1) is preferred from the viewpoint of providing a more excellent relative dielectric constant of the composition.

[0105] Formula (1) (CN-CH2CH2) n -L

[0106] L represents an n-valent linking group,

[0107] The n-valent linking group represented by L is not particularly limited, and examples thereof include aliphatic hydrocarbon groups, aromatic hydrocarbon groups, heterocyclic groups, -O-, -C(=O)-O-, -C(=O)-, -NH-, -S-, and groups formed by combining these.

[0108] n represents an integer of 1 to 50. Preferably n is 2 to 40, more preferably 3 to 30.

[0109] In addition, the compound represented by formula (1) is also represented by "L-(CH2CH2-CN) n ”.

[0110] The n-valent linking group is preferably a residue obtained by removing a hydrogen atom from a hydroxyl group in a compound selected from the group consisting of sugar compounds and sugar alcohols.

[0111] The sugar compound may be either a monosaccharide or a polysaccharide.

[0112] Examples of the sugar compound include sucrose, sorbitol, raffinose, cyclodextrin, cellulose, glucose, galactose, arabinose, xylose, maltose, cellobiose, isomaltose, lactose, sucrose, and fructose.

[0113] Examples of sugar alcohols include sorbitol, mannitol, arabitol, and xylitol.

[0114] In addition, structural formulas of cyano group-containing compounds are shown below in order from the left when the n-valent linking group is a residue obtained by removing a hydrogen atom from a hydroxyl group of sucrose, a residue obtained by removing a hydrogen atom from a hydroxyl group of sorbitol, and a residue obtained by removing a hydrogen atom from a hydroxyl group of raffinose.

[0115] [Chemical formula 3]

[0116]

[0117] As the cyano group-containing compound, cyanoethylsucrose represented by the leftmost structural formula in the above structural formula is preferred.

[0118] The content of the cyano group-containing compound in the composition is not particularly limited, but is preferably 1 to 99% by mass, more preferably 5 to 50% by mass, relative to the total mass of the composition. From the viewpoint of suppressing the generation of wrinkles in a film formed using the composition, it is further preferably 5 to 40% by mass. From the viewpoint of reducing the change in relative dielectric constant before and after the composition is exposed to a high temperature and high humidity environment, it is particularly preferably 5% by mass or more and less than 30% by mass, and most preferably 5 to 20% by mass.

[0119] The total content of the polymer and the cyano-containing compound in the composition is not particularly limited, but from the viewpoint of a better relative dielectric constant of the composition, the total content is preferably 80% by mass or more, more preferably 90% by mass or more relative to the total mass of the composition. The upper limit of the total content is not particularly limited, and 100% by mass can be cited.

[0120] The content ratio of the polymer to the cyano group-containing compound in the composition is not particularly limited, but the mass ratio of the polymer content to the cyano group-containing compound content is preferably 0.5 to 40, more preferably 3 to 30.

[0121] The above composition may contain other compounds in addition to the above polymer and cyano group-containing compound.

[0122] As other compounds, other dielectric polymers other than the above polymers and cyano-containing compounds can be cited. As other dielectric polymers, fluorine-based polymers such as polyvinylidene fluoride, vinylidene fluoride-tetrafluoroethylene copolymers, vinylidene fluoride-trifluoroethylene copolymers, polyvinylidene fluoride-trifluoroethylene copolymers, and polyvinylidene fluoride-tetrafluoroethylene copolymers can be cited.

[0123] Furthermore, examples of other compounds include tackifiers such as rosin ester, rosin, terpene, terpene phenol, and petroleum resin.

[0124] As other components, a solvent may also be mentioned. As the solvent, water and an organic solvent may be mentioned.

[0125] In addition, the composition preferably contains substantially no solvent. Substantially containing no solvent means that the content of the solvent is 1% by mass or less relative to the total mass of the composition.

[0126] The glass transition temperature of the composition is not particularly limited, but is preferably 5° C. or higher, more preferably 10° C. or higher, further preferably 20° C. or higher, and particularly preferably 30° C. or higher, from the viewpoint of better shape characteristics of a film containing the composition. The upper limit is not particularly limited, but is preferably 60° C. or lower, more preferably 50° C. or lower, from the viewpoint of operability.

[0127] The method for measuring the glass transition temperature of the composition is the same as the method for measuring the glass transition temperature of the polymer.

[0128] <Composite piezoelectric body>

[0129] The composite piezoelectric body of the present invention includes the above-mentioned polymer and piezoelectric particles.

[0130] The description of the polymer is as described above.

[0131] The content of the polymer in the composite piezoelectric body is not particularly limited, but is preferably 1 to 50% by mass, more preferably 2 to 30% by mass, based on the total mass of the composite piezoelectric body.

[0132] The piezoelectric particles are preferably dispersed in the above-mentioned polymer.

[0133] As the piezoelectric particles, ceramic particles having a perovskite-type or wurtzite-type crystal structure are preferred.

[0134] Examples of materials that constitute the piezoelectric particles include lead zirconate titanate (PZT), lead lanthanum zirconate titanate (PLZT), barium titanate (BaTiO3), zinc oxide (ZnO), and a solid solution (BFBT) of barium titanate and bismuth ferrite (BiFe3).

[0135] The particle size of the piezoelectric particles may be appropriately selected depending on the application of the composite piezoelectric body. The particle size of the piezoelectric particles is preferably 1 to 10 μm.

[0136] The content of the piezoelectric particles in the composite piezoelectric body is not particularly limited, but is preferably 30 to 99% by mass, more preferably 50 to 95% by mass, based on the total mass of the composite piezoelectric body.

[0137] The volume fraction of the piezoelectric particles in the composite piezoelectric body is not particularly limited, but is preferably 30 to 80 volume %, more preferably 50 to 80 volume %, relative to the total volume of the composite piezoelectric body.

[0138] The total content of the polymer and the piezoelectric particles in the composite piezoelectric body is not particularly limited, and the total content is preferably 80% by mass or more, more preferably 90% by mass or more, relative to the total mass of the composite piezoelectric body. The upper limit of the total content is not particularly limited, and 100% by mass may be cited.

[0139] The content ratio of the polymer to the piezoelectric particles in the composite piezoelectric body is not particularly limited, but the mass ratio of the content of the piezoelectric particles to the content of the polymer is preferably 1-30, and more preferably 3-20.

[0140] The composite piezoelectric body may contain other compounds in addition to the above-mentioned polymer and piezoelectric particles.

[0141] Examples of other compounds include the above-mentioned cyano group-containing compounds and other dielectric polymers.

[0142] Furthermore, examples of other compounds include tackifiers such as rosin ester, rosin, terpene, terpene phenol, and petroleum resin.

[0143] <Piezoelectric film>

[0144] The piezoelectric film of the present invention includes a piezoelectric layer including a composite piezoelectric body and electrode layers provided on both surfaces of the piezoelectric layer.

[0145] Figure 1 2 is a cross-sectional view schematically showing an example of the piezoelectric film of the present invention.

[0146] like Figure 1 As shown, the piezoelectric film 10 of the present invention has a piezoelectric layer 12 as a sheet, a first electrode layer 14 stacked on one surface of the piezoelectric layer 12, a first protective layer 18 stacked on the first electrode layer 14, a second electrode layer 16 stacked on the other surface of the piezoelectric layer 12, and a second protective layer 20 stacked on the second electrode layer 16.

[0147] The first electrode layer 14 and the second electrode layer 16 are provided in order to apply a voltage to the piezoelectric layer 12 (piezoelectric thin film 10 ).

[0148] The region sandwiched between the first electrode layer 14 and the second electrode layer 16 expands and contracts according to the applied voltage.

[0149] Hereinafter, each component included in the piezoelectric film 10 will be described in detail.

[0150] (Piezoelectric layer)

[0151] The piezoelectric layer 12 includes the above-mentioned composite piezoelectric body. More specifically, Figure 1 As shown, in the piezoelectric layer 12 , the piezoelectric particles 26 are preferably dispersed in a high molecular matrix 24 composed of a polymer.

[0152] The composite piezoelectric body is as described above.

[0153] The content of the composite piezoelectric body in the piezoelectric layer 12 is not particularly limited, but is preferably 80% by mass or more, more preferably 90% by mass or more, based on the total mass of the piezoelectric layer. The upper limit is not particularly limited, and may be 100% by mass.

[0154] The volume fraction of the piezoelectric particles in the piezoelectric layer 12 is not particularly limited, but is preferably 30 to 80 volume %, more preferably 50 to 80 volume %, relative to the total volume of the piezoelectric layer.

[0155] The content ratio of the polymer to the piezoelectric particles in the piezoelectric layer 12 is not particularly limited, but the mass ratio of the content of the piezoelectric particles to the content of the polymer is preferably 1-30, and more preferably 3-20.

[0156] Furthermore, the thickness of the piezoelectric layer 12 is not limited and may be appropriately set according to the size of the piezoelectric film, the application of the piezoelectric film, the characteristics required of the piezoelectric film, and the like.

[0157] The thickness of the piezoelectric layer 12 is not particularly limited, but is preferably 8 to 300 μm, more preferably 8 to 40 μm, from the viewpoint of ensuring both the rigidity of the piezoelectric film and appropriate flexibility.

[0158] The piezoelectric layer 12 is preferably subjected to polarization treatment (poling) in the thickness direction.

[0159] (Electrode layer)

[0160] The materials for forming the first electrode layer 14 and the second electrode layer 16 are not limited, and various conductors can be used. Examples of the above-mentioned forming materials include metals such as carbon, palladium, iron, tin, aluminum, nickel, platinum, gold, silver, copper, titanium, chromium, and molybdenum, their alloys, laminates and composites of these metals and alloys, and indium tin oxide. Alternatively, examples of the above-mentioned forming materials include conductive polymers such as PEDOT / PPS (polyethylene dioxythiophene-polystyrene sulfonic acid).

[0161] Among them, copper, aluminum, gold, silver, platinum, or indium tin oxide is preferable as a material for forming the first electrode layer 14 and the second electrode layer 16. Among them, copper is more preferable from the viewpoints of conductivity, cost, flexibility, and the like.

[0162] The thickness of the first electrode layer 14 and the second electrode layer 16 is not particularly limited. Furthermore, the thickness of the first electrode layer 14 and the second electrode layer 16 is substantially the same, but may be different.

[0163] In the piezoelectric film 10 , when the product of the thickness and Young's modulus of the first electrode layer 14 and the second electrode layer 16 is lower than the product of the thickness and Young's modulus of the first protective layer 18 and the second protective layer 20 , flexibility is not seriously impaired, which is preferred.

[0164] For example, when the first protective layer 18 and the second protective layer 20 are PET (Young's modulus: about 6.2 GPa), and the first electrode layer 14 and the second electrode layer 16 are composed of copper (Young's modulus: about 130 GPa), if the thickness of the first protective layer 18 and the second protective layer 20 is 25 μm, the thickness of the first electrode layer 14 and the second electrode layer 16 is preferably less than 1.2 μm, more preferably less than 0.3 μm, and further preferably less than 0.1 μm.

[0165] (Protective layer)

[0166] The first protective layer 18 and the second protective layer 20 play the role of covering the first electrode layer 14 and the second electrode layer 16 and giving appropriate rigidity and mechanical strength to the piezoelectric layer 12. That is, in the piezoelectric film 10, the piezoelectric layer 12 composed of the polymer matrix 24 and the piezoelectric particles 26 shows very excellent flexibility for slow bending deformation, but there is a case where the rigidity or mechanical strength is insufficient depending on the application. The first protective layer 18 and the second protective layer 20 are provided in the piezoelectric film 10 to compensate for this situation.

[0167] The first protective layer 18 and the second protective layer 20 are not particularly limited, and various sheet-like materials can be used. As one example, various resin films can be preferably exemplified.

[0168] Among them, from the viewpoint of having excellent mechanical properties and heat resistance, preferred are resin films composed of polyethylene terephthalate (PET), polypropylene (PP), polystyrene (PS), polycarbonate (PC), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polyetherimide (PEI), polyimide (PI), polyethylene naphthalate (PEN), triacetyl cellulose (TAC) and cyclic olefin resins.

[0169] The thickness of the first protective layer 18 and the second protective layer 20 is not particularly limited. Furthermore, the thickness of the first protective layer 18 and the second protective layer 20 is substantially the same, but may be different.

[0170] From the viewpoint of simultaneously ensuring rigidity and appropriate flexibility, the thickness of the first protective layer 18 and the second protective layer 20 is preferably not more than twice the thickness of the piezoelectric layer 12 .

[0171] For example, when the thickness of the piezoelectric layer 12 is 50 μm and the first protective layer 18 and the second protective layer 20 are made of PET, the thickness of the first protective layer 18 and the second protective layer 20 is preferably 100 μm or less, more preferably 50 μm or less, and further preferably 25 μm or less.

[0172] In the present invention, the piezoelectric film may have, in addition to the above-mentioned layers, for example, an adhesive layer for bonding the electrode layer and the piezoelectric layer, and an adhesive layer for bonding the electrode layer and the protective layer.

[0173] The adhesive may be an adhesive or a binder. Furthermore, the adhesive may preferably be made of the same material as the polymer material, i.e., the matrix, from which the piezoelectric particles are removed from the piezoelectric layer. In addition, the adhesive layer may be provided on both the first electrode layer side and the second electrode layer side, or may be provided on only one of the first electrode layer side and the second electrode layer side.

[0174] The piezoelectric film of the present invention preferably has a local maximum value of loss tangent (Tan δ) at a frequency of 1 Hz obtained by dynamic viscoelasticity measurement at room temperature, and more preferably has a local maximum value of 0.1 or more at room temperature.

[0175] Therefore, even if the piezoelectric film is subjected to relatively slow and large bending deformation of several Hz or less from the outside, the strain energy can be effectively diffused to the outside as heat, thereby preventing cracks from being generated at the interface between the matrix and the piezoelectric particles.

[0176] In the piezoelectric thin film, the storage elastic modulus (E') at a frequency of 1 Hz obtained by dynamic viscoelasticity measurement is preferably 10 to 30 GPa at 0° C. and 1 to 10 GPa at 50° C. The conditions are the same as those for the piezoelectric layer.

[0177] Thus, the piezoelectric film 10 can have a large frequency dispersion in the storage elastic modulus (E') at room temperature, that is, it can exhibit hardness for vibrations of 20 Hz to 20 kHz and exhibit softness for vibrations of several Hz or less.

[0178] In addition, the piezoelectric film preferably has a thickness and a storage elastic modulus (E') at a frequency of 1 Hz obtained by dynamic viscoelasticity measurement and a product of 1.0×10 5 ~2.0×10 6 N / m, 1.0×10 at 50°C 5 ~1.0×10 6 N / m. Note that this condition is the same as that of the piezoelectric layer.

[0179] As a result, the piezoelectric film can have appropriate rigidity and mechanical strength within a range that does not impair flexibility and acoustic characteristics.

[0180] Furthermore, the piezoelectric thin film preferably has a loss tangent (Tan δ) of 0.05 or more at 25° C. and a frequency of 1 kHz in a master curve obtained by dynamic viscoelasticity measurement. This condition is the same as that of the piezoelectric layer.

[0181] This makes the frequency characteristics of the speaker using the piezoelectric film smooth, and reduces the amount of change in sound quality when the lowest resonance frequency f0 changes with changes in the curvature of the speaker.

[0182] In the present invention, the storage elastic modulus (Young's modulus) and loss tangent of the piezoelectric film and the piezoelectric layer may be measured by a known method. For example, the dynamic viscoelasticity measuring device DMS6100 manufactured by SII Nano Technology Inc. may be used for measurement.

[0183] As an example of the measurement conditions, the following are respectively illustrated: the measurement frequency is 0.1Hz to 20Hz (0.1Hz, 0.2Hz, 0.5Hz, 1Hz, 2Hz, 5Hz, 10Hz and 20Hz), the measurement temperature is -50 to 150°C, the heating rate is 2°C / minute (in a nitrogen atmosphere), the sample size is 40mm×10mm (including the clamp area), and the clamp spacing is 20mm.

[0184] (Method for manufacturing piezoelectric film)

[0185] Below, reference Figure 2 to Figure 4 , an example of a method for manufacturing the piezoelectric thin film 10 is described.

[0186] First, prepare Figure 2 The sheet 11a shown in the figure has a first electrode layer 14 formed on the surface of the first protective layer 18. Figure 4 FIG. 1 conceptually shows a sheet-like object 11 c in which the second electrode layer 16 is formed on the surface of the second protective layer 20 .

[0187] The sheet 11a can be made by forming a copper thin film or the like on the surface of the first protective layer 18 by vacuum evaporation, sputtering, plating, etc. as the first electrode layer 14. Similarly, the sheet 11c can be made by forming a copper thin film or the like on the surface of the second protective layer 20 by vacuum evaporation, sputtering, plating, etc. as the second electrode layer 16.

[0188] Alternatively, a commercially available sheet in which a copper thin film or the like is formed on a protective layer may be used as the sheet 11 a and / or the sheet 11 c .

[0189] The sheet-shaped object 11a and the sheet-shaped object 11c may be the same or different.

[0190] Then, if Figure 3 As shown, a coating material (coating composition) to be the piezoelectric layer 12 is applied onto the first electrode layer 14 of the sheet 11a and then cured to form the piezoelectric layer 12. Thus, a laminate 11b in which the sheet 11a and the piezoelectric layer 12 are laminated is produced.

[0191] As an example of a method for forming the piezoelectric layer 12 , there is a method using a coating material.

[0192] In this method, first, the above-mentioned polymer is dissolved in an organic solvent, and piezoelectric particles such as PZT particles are further added and stirred to prepare a coating material.

[0193] The organic solvent is not particularly limited, and various organic solvents such as dimethylformamide (DMF), methyl ethyl ketone (MEK), and cyclohexanone can be used.

[0194] After the sheet 11a is prepared and the coating is prepared, the coating is cast (coated) on the sheet 11a, and the organic solvent is evaporated and dried. Figure 3 As shown in FIG. 1 , a stacked body 11 b is produced in which the first electrode layer 14 is provided on the first protective layer 18 and the piezoelectric layer 12 is stacked on the first electrode layer 14 .

[0195] The method for casting the coating material is not particularly limited, and examples thereof include known methods (coating devices) such as a bar coater, a slide coater, and a doctor blade.

[0196] Furthermore, as long as the polymer is a substance that can be heated and melted, a molten material can be prepared by heating and melting the polymer and adding piezoelectric particles thereto, and then extruding the molten material to obtain a molten material. Figure 2 The sheet 11a shown is extruded in a sheet form and cooled, thereby producing a sheet such as Figure 3 The stacked body 11b is shown.

[0197] After forming the piezoelectric layer 12, a rolling process may be performed as necessary. The rolling process may be performed once or a plurality of times.

[0198] As is well known, calendaring is a process for flattening a surface by pressing it while heating it with a heat press or a heating roll.

[0199] Next, the piezoelectric layer 12 of the stacked body 11b having the first electrode layer 14 on the first protective layer 18 and the piezoelectric layer 12 formed on the first electrode layer 14 is subjected to a polarization treatment (poling). The polarization treatment of the piezoelectric layer 12 may be performed before the rolling treatment, but is preferably performed after the rolling treatment.

[0200] The method of polarization treatment of the piezoelectric layer 12 is not particularly limited, and a known method can be used. For example, electric field poling in which a direct current electric field is directly applied to an object to be polarized is exemplified. In addition, when electric field poling is performed, the second electrode layer 16 can be formed before the polarization treatment, and the electric field poling treatment can be performed using the first electrode layer 14 and the second electrode layer 16.

[0201] Furthermore, in the piezoelectric thin film 10 of the present invention, the polarization treatment is preferably performed in the thickness direction rather than in the surface direction of the piezoelectric layer 12 .

[0202] Then, if Figure 4 As shown in FIG. 1 , a sheet 11 c prepared in advance is stacked on the piezoelectric layer 12 side of the polarized laminate 11 b so that the second electrode layer 16 faces the piezoelectric layer 12 .

[0203] Furthermore, the laminate 11b and the sheet 11c are bonded together by heat pressing using a heating roller or the like in such a manner as to sandwich the first protective layer 18 and the second protective layer 20, thereby producing a laminate 11b and a sheet 11c. Figure 1 The piezoelectric film 10 is shown.

[0204] Alternatively, the laminate 11b and the sheet 11c may be bonded together using an adhesive, and preferably pressure-bonded to produce the piezoelectric film 10. The same material as the matrix of the piezoelectric layer 12 may be used as the adhesive.

[0205] The piezoelectric film 10 can be manufactured using cut sheet-shaped sheets 11 a and 11 c , and can be manufactured using a roll-to-roll process.

[0206] The manufactured piezoelectric film 10 can also be cut into a desired shape according to various uses.

[0207] Figure 5 2 is a conceptual diagram showing an example of a flat-plate type piezoelectric speaker using the piezoelectric film 10 .

[0208] The piezoelectric speaker 40 is a flat-plate type piezoelectric speaker that uses the piezoelectric film 10 as a vibration plate that converts an electrical signal into vibration energy. The piezoelectric speaker 40 can also be used as a microphone, a sensor, and the like.

[0209] The piezoelectric speaker 40 is configured to include a piezoelectric film 10 , a housing 42 , and a pressing cover 48 .

[0210] The housing 42 is a cylindrical frame body with one side open, formed of plastic or the like. A pipe 42a inserted through the housing 42 is provided on the side surface of the housing 42.

[0211] The pressing cover 48 is a frame body having a substantially L-shaped cross section, and is inserted and fitted into the open surface side of the housing 42 .

[0212] The piezoelectric speaker 40 covers the housing 42 with the piezoelectric film 10 to block the open surface, and the pressing cover 48 is fitted into the housing 42 from above the piezoelectric film 10, thereby airtightly blocking the open surface of the housing 42 with the piezoelectric film 10. In addition, an O-ring or the like for maintaining airtightness may be provided between the upper surface of the side wall of the housing 42 and the piezoelectric film 10 as required.

[0213] In this state, by extracting the air in the housing 42 from the pipe 42a, as shown in FIG. Figure 5 As shown, the piezoelectric film 10 is held in a concave state. Conversely, the piezoelectric film 10 may be held in a convex state by introducing air into the housing 42 through the tube 42a.

[0214] In the piezoelectric speaker 40 , when a driving voltage is applied to the first electrode layer 14 and the second electrode layer 16 , the piezoelectric film 10 expands in the in-plane direction. The piezoelectric film 10 , which has a concave shape due to the decompression, moves downward to absorb the expansion.

[0215] On the contrary, when the piezoelectric film 10 contracts in the in-plane direction by applying a driving voltage to the first electrode layer 14 and the second electrode layer 16 , the concave piezoelectric film 10 moves upward to absorb the contraction.

[0216] The piezoelectric speaker 40 generates sound by the vibration of the piezoelectric film 10 .

[0217] <Piezoelectric elements>

[0218] The piezoelectric element of the present invention includes the above-mentioned piezoelectric thin film.

[0219] The piezoelectric element may have a single piezoelectric thin film or may have a plurality of piezoelectric thin films. When a plurality of piezoelectric thin films are stacked, the number of stacked piezoelectric thin films may be two or four or more.

[0220] Furthermore, the piezoelectric film can be folded and stacked.

[0221] In the piezoelectric element, a power source for applying a driving voltage for causing the piezoelectric film to expand and contract, that is, supplying driving power, is connected to the first electrode layer and the second electrode layer of each piezoelectric film.

[0222] The power source is not particularly limited and may be a DC power source or an AC power source. In addition, the driving voltage may be appropriately set according to the thickness and forming material of the piezoelectric layer of the piezoelectric film, so as to appropriately drive the piezoelectric film.

[0223] The method of extracting electrodes from the first electrode layer and the second electrode layer is not particularly limited, and various known methods can be used.

[0224] As an example, there can be cited a method of connecting a conductor such as copper foil to the first electrode layer and the second electrode layer to lead the electrodes to the outside, and a method of forming through holes in the first protective layer and the second protective layer by laser or the like and filling the through holes with a conductive material to lead the electrodes to the outside.

[0225] As a preferable electrode extraction method, the method described in Japanese Patent Application Laid-Open No. 2014-209724 and the method described in Japanese Patent Application Laid-Open No. 2016-015354 are exemplified.

[0226] Furthermore, in the case where the piezoelectric element is a structure in which the piezoelectric film is folded and stacked, it is preferred that the piezoelectric film on the outermost surface has a protrusion protruding outward in the surface direction from the stacked portion of the stacked piezoelectric film, and a connection portion for connecting the first electrode layer and the second electrode layer to a power source is formed in the protrusion. In addition, the method for connecting the electrode layer and the wiring in the protrusion is not particularly limited, and various known methods can be used.

[0227] The piezoelectric film or piezoelectric element of the present invention can be attached to a vibration plate to serve as an electroacoustic transducer. In the electroacoustic transducer, the piezoelectric film is used as a so-called exciter that vibrates the vibration plate by expressing piezoelectricity according to an applied voltage.

[0228] The vibration plate preferably has flexibility to be able to be rolled. In the present invention, flexibility has the same meaning as generally interpreted as flexibility, indicating that it can be bent and flexed, and specifically, can be bent and stretched without being broken or damaged.

[0229] The vibration plate is not particularly limited, and various sheet-like objects (plate-like objects, films) can be used.

[0230] As an example, there can be illustrated resin films made of polyethylene terephthalate (PET), polypropylene (PP), polystyrene (PS), polycarbonate (PC), polyphenylene sulfide (PPS), polymethyl methacrylate (PMMA), polyetherimide (PEI), polyimide (PI), polyethylene naphthalate (PEN), triacetyl cellulose (TAC) and cyclic olefin resins, foamed plastics made of expanded polystyrene, expanded styrene and expanded polyethylene, veneers, cork boards, leathers such as cowhide, carbon sheets, various paperboards such as Japanese paper, various corrugated cardboard materials made by pasting other paperboards on one or both sides of corrugated paperboards, and thin film metals made of various metals such as stainless steel, aluminum, copper and nickel, and various alloys.

[0231] Furthermore, the vibration plate may be a composite material obtained by laminating thin film-like objects composed of these materials.

[0232] Furthermore, as long as the vibration plate has flexibility, display devices such as organic light emitting diode (OLED) displays, liquid crystal displays, micro LED (light emitting diode) displays, and inorganic light emitting diode displays, and projector screens can also be preferably used as the vibration plate.

[0233] An adhesive layer may be disposed between the piezoelectric film or the piezoelectric element and the vibration plate.

[0234] The thickness of the adhesive layer is not particularly limited, and may be appropriately set according to the material of the adhesive layer so as to obtain a sufficient adhesive force (adhesive force, adhesive strength).

[0235] The thickness of the adhesive layer after adhesion is preferably 0.1 to 50 μm, more preferably 0.1 to 30 μm, and even more preferably 0.1 to 10 μm.

[0236] As the adhesive layer, various known adhesive layers can be used.

[0237] Therefore, the adhesive layer may be a layer composed of an adhesive that has fluidity when pasted and then becomes solid, or a layer composed of an adhesive that is a soft solid state in a gel (rubbery) state when pasted and then remains in a gel state, or a layer composed of a material having the characteristics of both an adhesive and an adhesive. Furthermore, the adhesive (adhesive) may be any one of a moisture-curing adhesive, a thermoplastic adhesive, and a thermosetting adhesive. Furthermore, as the adhesive layer, a double-sided tape and an adhesive sheet may be used.

[0238] Example

[0239] Below, enumerate specific embodiment of the present invention, the present invention is described in more detail. In addition, the present invention is not limited to this embodiment, as long as do not depart from the purpose of the present invention, then can suitably change the material shown in the following embodiment, usage, ratio, processing content and processing step etc.

[0240] <Synthesis example 1>

[0241] CR-V (manufactured by Shin-Etsu Chemical Co., Ltd.) (11.2 g) and methyl ethyl ketone (MEK) (54 mL) were added to a 500 mL three-necked flask, and the obtained reaction solution was stirred. Then, sodium bicarbonate (16.9 g) and DMAP (4-dimethylaminopyridine) (0.035 g) were added to the reaction solution, and the obtained reaction solution was stirred. Then, a solution consisting of acetic anhydride (16.0 g) and MEK (13.4 mL) was added dropwise to the reaction solution, and the obtained reaction solution was heated to 80°C. After reacting for 2 hours, the reaction solution was cooled to 60°C, and after adding MEK (112 mL) to the reaction solution, water (14 mL) was further added dropwise. Then, water (112 mL) was further added to the obtained reaction solution, the organic phase was extracted, and the obtained organic phase was dried with magnesium sulfate. Then, the solvent was distilled off from the dried organic phase using an evaporator to obtain a MEK solution (42.4 g) containing the polymer (polymer 1) used in Example 1. The concentration of the polymer in the solution was 25.2% by mass.

[0242] <Synthesis example 2>

[0243] Except that the acetic anhydride (16.0 g) in the above-mentioned Synthesis Example 1 was changed to propionic anhydride (16.0 g), the same procedure as Synthesis Example 1 was followed to obtain a MEK solution (42.4 g) containing a polymer (polymer 2) used in Example 2. The concentration of the polymer represented by formula (I-2) in the solution was 25.2% by mass.

[0244] Specifically, the carbon number of R in the repeating unit represented by the above formula (B) and the content of the repeating unit were adjusted by using a predetermined amount of a predetermined raw material instead of acetic anhydride.

[0245] <Example 1>

[0246] The MEK solution (3 g) containing polymer 1 prepared in Synthesis Example 1 was added to a petri dish, and the petri dish was heated to 100° C. using a hot plate, and then dried at 100° C. for 6 hours under reduced pressure. The obtained film was peeled from the petri dish to obtain a single film.

[0247] <Examples 2 to 10, Comparative Examples 1 and 2>

[0248] MEK solutions containing polymers shown in Table 1 described later (polymer concentration: 25.2 mass %) were prepared, and single membranes were produced in the same manner as in Example 1.

[0249] <Evaluation>

[0250] (Relative dielectric constant)

[0251] A 2 cm×4 cm strip-shaped test piece was prepared from the single film produced in each of the examples and comparative examples.

[0252] The relative dielectric constant εr of the long test piece was measured by an LCR meter. The measurement temperature was 25° C. and the measurement frequency was 1 kHz. The measurement results are shown in Table 1.

[0253] (Humidity resistance test)

[0254] A 2 cm×4 cm strip-shaped test piece was prepared from the single film produced in each of the examples and comparative examples.

[0255] After the long test piece was left standing for 1 hour in an environment of 80% humidity and 60% temperature, changes in relative dielectric constant and appearance before and after the standing were examined and evaluated according to the following criteria.

[0256] A: No changes were observed in relative dielectric constant and appearance.

[0257] B: Although no change in relative dielectric constant was observed, traces such as creases remained.

[0258] C: A change in relative dielectric constant is observed.

[0259] (Tg evaluation)

[0260] The glass transition temperature of the polymer was measured by DMA (dynamic viscoelasticity measurement) using a dynamic viscoelasticity measuring device (Rheogel-E4000, manufactured by UBM Co., Ltd.). Specifically, a plate-like sample with a thickness of 0.2 mm, a width of 5 mm, and a length of 10 mm was prepared using the polymer to be measured, and the obtained sample was scanned at a temperature of -50 to 150° C., and the dynamic viscoelasticity measurement was performed with a pressure application cycle of 1 Hz, and the temperature showing the maximum tan δ value was set as the glass transition temperature.

[0261] (Shape Evaluation)

[0262] The single films produced in each embodiment and comparative example were visually observed to evaluate the occurrence of wrinkles. In the evaluation, the visual results were set as "A" for no shape defects (occurrence of wrinkles), "B" for some shape defects, and "C" for obvious occurrence of shape defects.

[0263] The "Polymer" column in Table 1 shows the structure of the polymer used in each Example and Comparative Example.

[0264] The "Type" column in the "Polymer" column shows the type of polymer used in each example and comparative example. For example, in Example 1, polymer 1 was used.

[0265] The "Backbone" column in the "Polymer" column indicates which of the following formulas (I-1), (I-2), (I-4), (I-6), (I-9), (I-10), (R-1) and (R-2) the repeating unit contained in the polymer used in each embodiment and comparative example corresponds to.

[0266] The columns "a", "b", and "c" in the "Polymer" column represent the values ​​of a, b, and c in the formula shown in the "Backbone" column. a, b, and c represent the content (mol %) of each repeating unit relative to all repeating units in the polymer.

[0267] Regarding Comparative Example 2 in Table 1, since the “shape evaluation” was “C”, the “humidity resistance evaluation” was not performed and is indicated as “-” in Table 1.

[0268] [Chemical formula 4]

[0269]

[0270] For example, in Table 1, polymer 1 refers to a polymer represented by the following formula. That is, it refers to a polymer in which the content of the repeating unit represented by formula (A) is 80 mol%, the content of the repeating unit represented by formula (B) in which R is a methyl group is 19 mol%, and the content of the repeating unit represented by formula (C) is 1 mol%.

[0271] [Chemical formula 5]

[0272]

[0273] [Table 1]

[0274]

[0275] As shown in the above table, the polymer of the present invention exhibits predetermined effects.

[0276] From the comparison of Examples 1 to 5, it was confirmed that when the carbon number of the aliphatic hydrocarbon group represented by R in the repeating unit represented by the formula (B) was 2 to 8, the moisture resistance evaluation was more excellent.

[0277] From the comparison between Examples 5 and 6, it was confirmed that when the aliphatic hydrocarbon group represented by R in the repeating unit represented by the formula (B) was linear, the shape evaluation was more excellent.

[0278] Comparison between Examples 2 and 7 showed that when the content of the repeating unit represented by the formula (A) was 70 mol % or more, the relative dielectric constant and the moisture resistance evaluation were more excellent.

[0279] <Examples 11 to 19>

[0280] A single membrane was prepared in the same manner as in Example 1 using a solution obtained by mixing an MEK solution and a cyano group-containing compound shown in Table 2, respectively, containing a polymer shown in Table 2 below (polymer concentration: 25.2 mass %).

[0281] The single film is composed of a polymer and a cyano-containing compound.

[0282] In addition, the cyano group-containing compounds used in Table 2 are as follows.

[0283] Cyanoethyl sucrose: manufactured by Shin-Etsu Chemical Co., Ltd., CR-U (cyano group content: 10.4 mmol / g)

[0284] ·Cyanoethyl sorbitol: synthetic product (refer to the synthesis method in the following section) (cyano content: 12.0 mmol / g)

[0285] ·Cyanoethyl β-cyclodextrin: synthetic product (refer to the synthesis method in the following section) (cyano content: 9.3mmol / g)

[0286] (Synthesis method of cyanoethylated sorbitol)

[0287] 3% sodium hydroxide solution (200g) was added to sorbitol (30g) to dissolve it, acrylonitrile (150g) was added to the obtained solution, and the obtained reaction solution was reacted at 40°C for 4 hours. After the reaction was completed, acetic acid (1.8g) was added to the obtained reaction solution to neutralize it and stop the reaction. Then, the obtained reaction solution was heated and unreacted acrylonitrile was distilled off. Then, dichloromethane (390g) was added to the residue to dissolve it, water (170mL) was added thereto and stirred, and then the mixture was allowed to stand to separate the liquid and the aqueous phase was removed. Then, the solvent in the organic phase obtained by the evaporator was distilled off to obtain a composition (70g) with transparent and viscous cyanoethylated sorbitol as the main component.

[0288] Cyanoethylated β-cyclodextrin was synthesized in the same manner as above except that cyclodextrin was used as a raw material instead of sorbitol.

[0289] The above-mentioned various evaluations were carried out using the single film obtained above. The results are summarized in Table 2.

[0290] In Table 2, the column "Content (mass %)" in the column "Cyanide-containing compound" indicates the content (mass %) of the cyanide-containing compound relative to the total amount of the single film.

[0291]

[0292] As shown in Table 2, it was confirmed that excellent effects were obtained in the composition containing the polymer of the present invention and the cyano group-containing compound.

[0293] From the comparison between Example 2 and Example 11, it was confirmed that the relative dielectric constant was more excellent when the cyano group-containing compound was used.

[0294] Comparison of Examples 11 to 15 showed that when the content of the cyano group-containing compound was 5 to 40% by mass, the shape evaluation was more excellent, and when the content of the cyano group-containing compound was 5 to 20% by mass, the moisture resistance evaluation was more excellent.

[0295] <Production of piezoelectric film>

[0296] Through the aforementioned Figure 2 to Figure 4 The method shown in the figure produced Figure 1 The piezoelectric film 10 is shown.

[0297] First, PZT particles were added at the following composition ratio to a 25 mass % MEK solution of a predetermined polymer used in Examples and Comparative Examples, and dispersed using a propeller mixer (rotation speed 2000 rpm) to prepare a coating material for forming a piezoelectric layer.

[0298] ·PZT particles················· 300 parts by mass

[0299] ·25.2 mass % MEK solution of a predetermined polymer······· 120 parts by mass

[0300] The PZT particles used were obtained by sintering a commercially available PZT raw material powder at 1000 to 1200° C., and then pulverizing and classifying the powder so as to have an average particle size of 5 μm.

[0301] On the other hand, two sheets (sheet 11a and sheet 11c) were prepared by vacuum evaporating a copper film with a thickness of 0.1 μm on a PET film with a thickness of 4 μm. That is, in this example, the first electrode layer 14 and the second electrode layer 16 were copper-evaporated films with a thickness of 0.1 μm, and the first protective layer 18 and the second protective layer 20 were PET films with a thickness of 4 μm.

[0302] The coating material for forming the previously prepared piezoelectric layer 12 was applied onto the copper-deposited film (first electrode layer 14) of the sheet (sheet 11a) using a slide coater. The coating material was applied so that the thickness of the coating film after drying would be 40 μm.

[0303] Next, the coating material applied on the copper vapor-deposited film (first electrode layer 14) was heated and dried on a hot plate at 120° C., thereby evaporating cyclohexanone. Thus, a laminate (laminate 11b) was prepared in which the first electrode layer 14 made of copper was provided on the first protective layer 18 made of PET and the piezoelectric layer 12 with a thickness of 40 μm was formed thereon.

[0304] The piezoelectric layer 12 of the stacked body 11b was polarized by corona polarization. The polarization was performed by setting the temperature of the piezoelectric layer 12 to 100°C and applying a DC voltage of 6 kV between the first electrode layer 14 and the corona electrode to generate corona discharge.

[0305] On the polarized laminate 11 b , the sheet 11 c is laminated with the second electrode layer 16 (copper thin film side) facing the piezoelectric layer 12 .

[0306] Next, the stacked body 11 b and the sheet-like object 11 c were thermocompressed at 120° C. using a laminating device, thereby bonding the piezoelectric layer 12 and the first electrode layer 14 and the second electrode layer 16 to produce the piezoelectric film 10 .

[0307] <Production of Piezoelectric Speakers>

[0308] A 70 mm φ circular test piece was cut out from the prepared piezoelectric film and the following Figure 5 The piezoelectric speaker shown.

[0309] The housing was a cylindrical container with one side open, and a plastic cylindrical container with an opening size of φ60 mm and a depth of 10 mm was used.

[0310] The piezoelectric film is arranged to cover the opening of the shell, and after the peripheral part is fixed by pressing the cover, the air is discharged from the shell through the duct, and the pressure in the shell is maintained at 0.09 MPa, so that the piezoelectric film is bent into a concave shape, thereby producing a piezoelectric speaker.

[0311] Industrial Applicability

[0312] Regarding the piezoelectric film and piezoelectric element of the present invention, for example, they can be preferably used as various sensors suitable for acoustic wave sensors, ultrasonic sensors, pressure sensors, tactile sensors, strain sensors and vibration sensors (especially useful for infrastructure inspection such as crack detection or manufacturing site inspection such as foreign matter mixing detection), audio devices such as microphones, pickups, speakers and exciters (as specific uses, examples include noise cancellers (used in cars, commuter trains, airplanes, robots, etc.), artificial vocal cords, buzzers for preventing pests / harmful animals from invading, furniture, wallpapers, photos, helmets, goggles, headrests, signs, robots, etc.), tactile interfaces for automobiles, smart phones, smart watches, game consoles, etc., ultrasonic transducers such as ultrasonic probes and underwater wave receivers; actuators used in preventing water droplet adhesion, transportation, stirring, dispersion and grinding; vibration-damping materials (dampers) used in containers, vehicles, buildings, sports equipment such as skis and rackets; and vibration power generation devices suitable for roads, floors, mattresses, chairs, shoes, tires, wheels and computer keyboards.

[0313] Explanation of symbols

[0314] 10-piezoelectric film, 11a, 11c-sheet, 11b-laminated body, 12-piezoelectric layer, 14-first electrode layer, 16-second electrode layer, 18-first protective layer, 20-second protective layer, 24-polymer matrix, 26-piezoelectric particles, 40-piezoelectric speaker, 42-shell, 48-frame.

Claims

1. A polymer comprising a repeating unit represented by formula (A) and a repeating unit represented by formula (B), wherein: The content of the repeating unit represented by formula (A) is 60 mol% or more relative to all the repeating units of the polymer, The content of the repeating unit represented by formula (B) is 1 to 40 mol% relative to all the repeating units of the polymer. The polymer does not contain a repeating unit represented by formula (C), or In the case where the polymer contains a repeating unit represented by the formula (C), the content of the repeating unit represented by the formula (C) is 5 mol% or less relative to all the repeating units of the polymer, [Chemical formula 1] R represents an aliphatic hydrocarbon group which may have a substituent, wherein the aliphatic hydrocarbon group which may have a substituent has 1 to 8 carbon atoms.

2. The polymer according to claim 1, wherein The aliphatic hydrocarbon group which may have a substituent has 2 to 8 carbon atoms.

3. The polymer according to claim 1, wherein The content of the repeating unit represented by formula (A) is 70 mol% or more relative to all the repeating units of the polymer, The content of the repeating unit represented by the formula (B) is 1 to 30 mol% relative to all the repeating units of the polymer. 4 . A composition comprising the polymer according to claim 1 and a cyano group-containing compound different from the polymer.

5. The composition according to claim 4, wherein The cyano group-containing compound is a compound represented by formula (1), Formula (1) (CN-CH2CH2) n -L L represents an n-valent linking group, where n represents an integer of 1-50.

6. The composition according to claim 4, wherein The cyano compound is cyanoethyl sucrose. 7 . A composite piezoelectric body comprising the polymer according to claim 1 and piezoelectric particles.

8. The composite piezoelectric body according to claim 7, wherein: The piezoelectric particles include ceramic particles having a perovskite-type or wurtzite-type crystal structure.

9. The composite piezoelectric body according to claim 7, wherein: The piezoelectric particles include any one of lead zirconate titanate, lead lanthanum zirconate titanate, barium titanate, zinc oxide, and a solid solution of barium titanate and bismuth ferrite. 10 . The composite piezoelectric body according to claim 7 , further comprising a cyano group-containing compound different from the polymer.

11. A piezoelectric film, comprising: A piezoelectric layer comprising the composite piezoelectric body according to claim 7; and Electrode layers are provided on both surfaces of the piezoelectric layer. 12 . A piezoelectric element comprising the piezoelectric film according to claim 11 .

Citation Information

Patent Citations

  • High dielectric substance

    JP1994196022A

  • Electroacoustic conversion film

    JP2014209724A

  • Electroacoustic conversion film and conduction method of the same

    JP2016015354A